Composite, method for producing the same, and cosmetic filling composition using the same

By using biodegradable particles with a mesh structure and a water-soluble polymer in the beauty filling composition, the cake-like dosage form complex is solved, and the problems of short shelf life and difficulty in injection in the prior art are achieved. Good storage and operability.

CN117615802BActive Publication Date: 2025-01-14KOREA FINI CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380012739.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-06-14
Filing Date
2023-06-14
Publication Date
2025-01-14
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

The existing cosmetic filling compositions have limited shelf life after use for a period of time, and are too high in viscosity or poor dispersion, resulting in difficulty in injection and discomfort and fatigue of the operator.

Method used

Using biodegradable particles and water-soluble polymers with a mesh structure inside to form a composite with a cake-like dosage form, the particles are formed by spraying a second solvent with a low freezing point and adding them to the water-soluble polymer, freezing Dry to form a complex.

Benefits of technology

It improves the long-term storage and dispersion of the complex, reduces the degradation of biodegradable particles and water-soluble polymers, extends the shelf life, simplifies the operation process, reduces the injection force requirement, and improves the convenience of the operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117615802B_ABST
    Figure CN117615802B_ABST
Patent Text Reader

Abstract

The present invention relates to a composite, a method for producing the composite, and a cosmetic filling composition using the composite, wherein the composite comprises biodegradable particles each having a network structure inside; and a water-soluble polymer. The composite has a cake-like dosage form, and thus has good long-term storage and dispersibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite composed of two or more components, a method for producing the composite, and a cosmetic filling composition (eg, a cosmetic filling composition for skin) using the composite. Background Art

[0002] Cosmetic surgery is to inject a filler composition into the subcutaneous tissue or tissue to achieve the purpose of correcting human function or beautifying the skin. The filler composition is preferably safe for the human body and has biocompatibility and biodegradability.

[0003] The filler composition contains natural polymers such as collagen, gelatin, hyaluronic acid and dextran, or synthetic polymers such as polylactic acid, polyglutamic acid, polycaprolactone and polyacrylamide.

[0004] However, since the natural polymer or the synthetic polymer begins to decompose after a period of use, the filling composition containing these polymers has a limited shelf life. In addition, most filling compositions are injected with a syringe, in which case, if the viscosity of the filling composition is too high or the dispersibility is poor, it is difficult to inject the filling composition with a fine needle, and the force of the syringe (injection force) must be increased, causing discomfort and fatigue to the operator.

[0005] [Prior art literature]

[0006] [Patent Document]

[0007] (Patent Document 1) Korean Patent Publication No. 2017-0123099 (November 7, 2017) Summary of the invention

[0008] Technical issues

[0009] The present invention aims to provide a composite having excellent long-term storage and dispersibility, which can improve the operating environment of a cosmetic filling composition, and a method for producing the composite.

[0010] Furthermore, the present invention is also intended to provide a cosmetic filling composition that can be operated on relatively easily.

[0011] Means of solving the problem

[0012] To solve the above problems, according to one embodiment of the present invention, the present invention provides a composite, which includes biodegradable particles each having a network structure inside; and a water-soluble polymer, and has a cake-like dosage form.

[0013] According to another embodiment of the present invention, a method for manufacturing a composite is provided, comprising the following steps:

[0014] (1) dissolving a biodegradable raw material in a first solvent to prepare a biodegradable solution; (2) spraying the biodegradable solution into a second solvent having a freezing point lower than that of the first solvent to form biodegradable particles having a network structure inside; (3) screening the biodegradable particles according to size; (4) adding the biodegradable particles screened by size to a water-soluble polymer solution to prepare a mixed solution; (5) filling the mixed solution into a container; and (6) freeze-drying the mixed solution filled into the container to form a complex having a cake-like dosage form.

[0015] According to another embodiment of the present invention, a cosmetic filling composition containing the complex is provided.

[0016] Effects of the Invention

[0017] The composite according to the present invention has a cake-like dosage form with a fluffy texture, and contains biodegradable particles with a network structure inside, which enables it to be quickly and evenly dispersed when dispersed in a solvent. In addition, since the composite of the present invention has a cake-like dosage form with a solid phase, the degradation of the biodegradable particles and / or water-soluble polymer contained in the composite can be minimized even during long-term storage. Therefore, when the composite according to the present invention is used as a material in a cosmetic filling composition, the shelf life of the material can be extended, storage is facilitated, and handling is improved.

[0018] Furthermore, since the cosmetic filling composition according to the present invention is a highly dispersed complex, the surgical procedure can be easily performed even if the operator (operator) applies relatively small force to the syringe.

[0019] Simple diagram description

[0020] Figure 1 is a schematic diagram of a manufacturing process of a composite according to an embodiment of the present invention;

[0021] Figure 2 It is a photograph of the composite dosage form according to Example 1, Example 5 and Comparative Example 1 in Confirmation Experimental Example 1;

[0022] Figure 3is a picture of a cross section of the composite according to Example 1 confirmed by scanning electron microscopy in Experimental Example 2;

[0023] Figure 4 This is a picture of a cross section of the composite according to Example 5 confirmed by a scanning electron microscope in Experimental Example 2.

[0024] Best Mode for Carrying Out the Invention

[0025] The present invention will be described in detail below, wherein the present invention is not limited to the contents disclosed below but can be modified in various forms without changing the essence of the present invention.

[0026] The word "comprising" in this specification is intended to specify certain features, regions, steps, processes, elements and / or components, and does not exclude the existence or addition of other features, regions, steps, processes, elements and / or components unless specifically stated to the contrary.

[0027] Whenever it is mentioned in the present specification that one component is connected or coupled to another component, any connection or coupling between the components directly or indirectly connected or coupled through the presence of the other component is included.

[0028] In this specification, unless the context indicates otherwise, a singular expression should be construed as including the singular or the plural.

[0029] Unless otherwise indicated, all numbers and expressions indicating amounts of ingredients, reaction conditions, etc. in this specification may be expressed as "about".

[0030] The terms "first", "second" and the like in the present specification are used to describe various components, and each component is not limited by these terms, and these terms are only used to distinguish one component from another.

[0031] Compound

[0032] The composite of the present invention can be a combination of materials with biocompatibility and / or biodegradability. Specifically, the composite of the present invention includes biodegradable particles with a network structure inside; and a water-soluble polymer, which has a cake-like dosage form, as described below.

[0033] Biodegradable particles

[0034] According to the present invention, the biodegradable particles contained in the composite have the function of restoring or replacing damaged or aged human tissues (such as skin tissues).

[0035] The biodegradable particles may be particles with a reticular structure. Specifically, the interior of the biodegradable particles may form a regular, irregular or combined three-dimensional network structure. Since the reticular structure exists inside the biodegradable particles, the biodegradable particles have high strength, thereby effectively repairing or replacing human tissue. In addition, since the biodegradable particles have high strength, the strength of the composite composed of the biodegradable particles will also increase, thereby improving the handling convenience of the composite.

[0036] The biodegradable particles may include a common biodegradable polymer. Specifically, the biodegradable particles may include at least one selected from the group consisting of polylactic acid (PLA), polyglycolic acid (PGA), poly(D,L-lactic-coglycolic acid) (PLGA), polycaprolactone (PCL), polyvalerolactone (PVL), polyhydroxybutyrate (PHB) and polyhydroxyvalerate (PBV), but are not limited thereto. Preferably, the biodegradable particles are polylactic acid (PLA) particles.

[0037] The weight average molecular weight of the biodegradable particles may be 50,000 to 400,000 g / mol, but is not limited thereto. Specifically, the weight average molecular weight of the biodegradable particles may be 60,000 to 350,000 g / mol, 70,000 to 300,000 g / mol, 90,000 to 250,000 g / mol, 100,000 to 200,000 g / mol, 130,000 to 190,000 g / mol, or 150,000 to 180,000 g / mol. Since the weight average molecular weight of the biodegradable particles is within the above range, it is easy to process into a composite and the dispersibility of the composite can be improved.

[0038] The tap density (Tab Density) of the biodegradable particles may be 0.1 to 0.25 g / ml, but is not limited thereto. Specifically, the tap density of the biodegradable particles may be 0.1 to 0.24 g / ml, 0.11 to 0.23 g / ml, 0.12 to 0.21 g / ml, 0.13 to 0.18 g / ml, or 0.13 to 0.17 g / ml. Since the tap density of the biodegradable particles is within the above range, the biodegradable particles can be densely distributed in the composite, thereby increasing the strength of the composite and improving the dispersibility of the composite.

[0039] Meanwhile, the particle size distribution (PSD) of the biodegradable particles may be 0.4 to 2.5, 0.5 to 2.2, 0.6 to 2.0, 0.65 to 1.9, 0.7 to 1.8, 0.8 to 1.7, 1.0 to 2.5, 1.0 to 2.3, 1.0 to 2.0, 1.01 to 1.6, 1.02 to 1.5, 1.03 to 1.4, or 1.05 to 1.3, but is not limited thereto, according to the following formula 1. Since the particle size distribution of the biodegradable particles is within the above range, the dispersibility of the composite in the solvent can be very excellent. In addition, when the composite is used as a material for a cosmetic filling composition, even with a thinner injection needle, only a small force needs to be applied to the syringe to successfully inject the cosmetic filling composition.

[0040] <Formula 1>

[0041] PSD = (Dv(90) - Dv(10)) / Dv(50)

[0042] In the formula 1,

[0043] Dv(10) is the size of the biodegradable particles within 10% of the distribution (based on the distribution of biodegradable particles, the particle size is arranged from small to large based on volume, and the particle size is located at the 10% position),

[0044] Dv(50) is the size of the biodegradable particles within 50% of the distribution (based on the distribution of biodegradable particles, the particle size is arranged from small to large based on volume, and the particle size is located at the 50% position),

[0045] Dv(90) is the size of the 90% biodegradable particle distribution (based on the biodegradable particle distribution, the particle size is arranged from small to large based on volume, and the particle size is located at the 90% position).

[0046] Specifically, in Formula 1, Dv(10) may be 5 to 35 μm, 7 to 33 μm, 10 to 30 μm, 11 to 28 μm, 12 to 25 μm or 12 to 22 μm, Dv(50) may be 10 to 50 μm, 13 to 47 μm, 15 to 45 μm, 17 to 43 μm, 19 to 42 μm or 20 to 42 μm, and Dv(90) may be 20 to 90 μm, 25 to 85 μm, 27 to 82 μm, 29 to 80 μm, 30 to 78 μm or 32 to 75 μm, but is not limited thereto.

[0047] Water soluble polymer

[0048] According to the present invention, the water-soluble polymer contained in the composite has a carrier function for transporting the biodegradable particles, and a matrix function for dispersing and fixing the biodegradable particles.

[0049] The water-soluble polymer may include well-known polymers with water solubility. Specifically, the water-soluble polymer may include at least one selected from the combination consisting of hyaluronic acid (HA), methylcellulose (MC), ethylcellulose (EC), carboxymethylcellulose (CMC), hydroxymethylcellulose (HMC), hydroxyethylcellulose (HEC), hydroxypropylcellulose (HPC), hydroxymethyl methacrylate (HEMA), polyvinyl alcohol (PVOH), polyvinyl pyrrolidone (PVP) and starch, but is not limited thereto. Preferably, the water-soluble polymer is hyaluronic acid (HA). Specifically, the water-soluble polymer may be non-crosslinked hyaluronic acid.

[0050] The hyaluronic acid (HA) can be a high molecular weight hyaluronic acid, such as sodium hyaluronate crosspolymer and sodium hyaluronate; a medium molecular weight hyaluronic acid, such as hydroxypropyltrimonium hyaluronate and sodium acetylated hyaluronate; a low molecular weight hyaluronic acid, such as potassium hyaluronate, hydrolyzed hyaluronic acid and hydrolyzed sodium hyaluronate; an ultra-low molecular weight hyaluronic acid, such as hyaluronic acid; or a combination thereof.

[0051] The weight average molecular weight of the water-soluble polymer may be 1,000,000 to 4,000,000 g / mol, but is not limited thereto. Specifically, the weight average molecular weight of the water-soluble polymer may be 1,200,000 to 4,000,000 g / mol, 1,300,000 to 4,000,000 g / mol, 1,500,000 to 4,000,000 g / mol, 1,800,000 to 4,000,000 g / mol, 2,000,000 to 4,000,000 g / mol, 2,100,000 to 3,800,000 g / mol or 2,200,000 to 3,600,000 g / mol. Since the weight average molecular weight of the water-soluble polymer is within the above range, it is easy to be processed into a composite and the dispersibility of the composite can be improved.

[0052] According to the present invention, the weight ratio of the biodegradable particles to the water-soluble polymer may be 40:60 to 95:5, but is not limited thereto. Specifically, the weight ratio of the biodegradable particles to the water-soluble polymer contained in the composite may be 45:55 to 95:5, 45:55 to 90:10, 50:50 to 90:10, 55:45 to 85:15, 60:40 to 85:15, 65:35 to 85:15, 70:30 to 85:15, 75:25 to 85:15, 80:20 to 85:15 or 70:30 to 80:20. Since the weight ratio is within the above range, the composite has excellent dispersibility and can be effectively used as a material for a cosmetic filling composition.

[0053] Meanwhile, the composite according to the present invention may have a compressive strength of 0.02 to 1.5 MPa, but is not limited thereto. Specifically, the compressive strength of the composite according to the present invention may be 0.025 to 1.3 MPa, 0.03 to 1.2 MPa, 0.033 to 1.0 MPa, 0.035 to 1.0 MPa, 0.035 to 0.8 MPa, 0.035 to 0.6 MPa, 0.036 to 0.5 MPa, 0.036 to 0.45 MPa, 0.036 to 0.43 MPa, 0.037 to 0.4 MPa, 0.037 to 0.39 MPa, 0.037 to 0.38 MPa or 0.037 to 0.37 MPa.

[0054] In addition, the apparent volume of the composite according to the present invention may be 10 to 40 ml / g, but is not limited thereto. Specifically, the apparent volume of the composite according to the present invention may be 10 to 35 ml / g, 10 to 32 ml / g, 10 to 30 ml / g, 12 to 29 ml / g, 14 to 29 ml / g, 15 to 28 ml / g, 15.5 to 28 ml / g or 16 to 28 ml / g.

[0055] In addition, the porosity of the composite according to the present invention may be 90 to 97.5% by volume, but is not limited thereto. Specifically, the porosity of the composite according to the present invention may be 90 to 97% by volume, 90 to 96% by volume, or 90 to 95% by volume. The porosity may refer to the ratio of the pore volume present in the composite to the total volume of the composite.

[0056] Since the composite of the present invention has the compressive strength, apparent density and porosity within the above-mentioned specific ranges, it can have excellent long-term storage, handling convenience and dispersibility. In particular, since the compressive strength of the composite according to the present invention is adjusted within the above-mentioned specific range, when the composite is dispersed in a solvent for preparing a cosmetic filling composition, it can be uniformly dispersed in a short time.

[0057] Specifically, the suspension time of the complex according to the present invention in an aqueous solvent can be 30 minutes or less, but is not limited thereto. More specifically, the suspension time of the complex according to the present invention in an aqueous solvent can be 1 to 30 minutes, 5 to 30 minutes, 10 to 30 minutes, 10 to 29 minutes, 10 to 25 minutes, 10 to 20 minutes or 12 to 19 minutes. At this time, the aqueous solvent can specifically be water, distilled water, deionized water, ultrapure water, etc., but is not limited thereto.

[0058] According to the present invention, the composite can have a cake formulation with a fluffy texture. Since the composite has a cake formulation, it can have good long-term storage and dispersibility in a solvent.

[0059] Specifically, the composite of the present invention may be cylindrical, but is not limited thereto. In addition, the average diameter of the composite may be 1 to 5 cm, 1 to 3 cm, 1 to 2.5 cm, 1.2 to 2.2 cm, or 1.5 to 2.0 cm, and the average height of the composite may be 0.2 to 5 cm, 0.3 to 3 cm, 0.5 to 3 cm, or 0.5 to 2.5 cm, but is not limited thereto.

[0060] Method for producing composite material

[0061] The present invention provides a method for manufacturing the composite. Specifically, the method for manufacturing the composite according to the present invention comprises the following steps: (1) dissolving a biodegradable raw material in a first solvent to prepare a biodegradable solution; (2) spraying the biodegradable solution into a second solvent having a freezing point lower than that of the first solvent to form biodegradable particles having a mesh structure inside; (3) screening the biodegradable particles according to size; (4) adding the biodegradable particles screened by size to a water-soluble polymer solution to prepare a mixed solution; (5) filling the mixed solution into a container; and (6) freeze-drying the mixed solution filled into the container to form a composite having a cake-like dosage form.

[0062] The step (1) is a step of dissolving the biodegradable raw material in a first solvent to prepare a biodegradable solution. Specifically, the step (1) can be achieved by adding the biodegradable raw material into a first solvent mixed with two or more organic solvents and stirring.

[0063] Specifically, the biodegradable raw material may include at least one selected from the group consisting of polylactic acid (PLA), polyglycolic acid (PGA), poly(D,L-lactic acid-coglycolic acid) (PLGA), polycaprolactone (PCL), polyvalerolactone (PVL), polyhydroxybutyrate (PHB) and polyhydroxyvalerate (PBV), but is not limited thereto.

[0064] The weight average molecular weight of the biodegradable raw material may be 50,000 to 400,000 g / mol, but is not limited thereto. Specifically, the weight average molecular weight of the biodegradable particles may be 60,000 to 350,000 g / mol, 70,000 to 300,000 g / mol, 90,000 to 250,000 g / mol, 100,000 to 200,000 g / mol, 130,000 to 190,000 g / mol, or 150,000 to 180,000 g / mol.

[0065] The first solvent can specifically be a combination of at least two substances selected from the following substances: dimethyl sulfoxide, diethyl sulfoxide, ethylene carbonate, propylene carbonate, dimethyl carbonate, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-hydroxyethyl-2-pyrrolidone, N-cyclohexyl-2-pyrrolidone, N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-ethylformamide, N-methylacetamide, N,N-dimethylacetamide, N,N-diethylacetamide, isopropyl acetate, ethyl acetate, methyl acetate, dimethyl ketone, diethyl ketone, methyl ethyl ketone, isopropyl ketone, methyl propyl ketone, methyl butyl ketone, methyl isobutyl ketone and tetrahydrofuran, but is not limited thereto.

[0066] Specifically, the first solvent may be a first organic solvent and a second organic solvent mixed in a weight ratio of 70:30 to 98:2, 75:25 to 98:2, 80:20 to 95:5, 85:15 to 95:5, or 85:15 to 90:10. More specifically, the first solvent may be a mixed solvent of dimethyl sulfoxide and ethylene carbonate, but is not limited thereto.

[0067] The step (2) is a step of spraying the biodegradable solution into a second solvent having a lower freezing point than the first solvent to form biodegradable particles having a network structure inside. Specifically, the step (2) can be achieved by spraying the biodegradable solution into a second solvent, the second solvent is not mixed with the first solvent to achieve phase separation, and its freezing point is 50 to 150° C. (specifically, 90 to 120° C.) lower than the freezing point of the first solvent.

[0068] When spraying, the temperature of the second solvent may be specifically -45 to 0° C., -40 to -5° C., -35 to -10° C., or -30 to -10° C., but is not limited thereto. Since the temperature of the second solvent is within the above range, biodegradable particles having a desired particle size distribution and a network structure can be well formed.

[0069] The second solvent may be at least one selected from the group consisting of pentane, hexane, heptane, octane, nonane and decane, but is not limited thereto.

[0070] The spraying speed of the biodegradable solution into the second solvent may be 1 to 20 ml / min, 3 to 15 ml / min, or 5 to 10 ml / min, but is not limited thereto.

[0071] The step (3) is a step of screening the biodegradable particles according to size. Specifically, the step (3) can be achieved by feeding the biodegradable particles into a particle sorting machine to select particles with a desired size.

[0072] The size of the biodegradable particles selected by the particle sorter is not particularly limited, but the size can be selected according to Dv(50) (average particle diameter) of 10 to 60 μm (specifically, 13 to 47 μm or 15 to 45 μm). Through this step, the particle size distribution of the biodegradable particles can be adjusted to a specific range, and when a composite is prepared using the biodegradable particles having a controlled particle size distribution, a composite having good dispersibility in a solvent can be provided.

[0073] The step (4) is a step of adding the biodegradable particles selected by size to a water-soluble polymer solution to prepare a mixed solution. Specifically, the step (4) can be achieved by adding the biodegradable particles selected by size to a water-soluble polymer solution with a controllable concentration and stirring.

[0074] The water-soluble polymer contained in the water-soluble polymer solution may specifically include at least one polymer selected from the following combinations: hyaluronic acid (HA), methyl cellulose (MC), ethyl cellulose (EC), carboxymethyl cellulose (CMC), hydroxymethyl cellulose (HMC), hydroxyethyl cellulose (HEC), hydroxypropyl cellulose (HPC), hydroxymethyl methacrylate (HEMA), polyvinyl alcohol (PVOH), polyvinyl pyrrolidone (PVP) and starch, but is not limited thereto.

[0075] The weight average molecular weight of the water-soluble polymer may be 1,000,000 to 4,000,000 g / mol, but is not limited thereto. Specifically, the weight average molecular weight of the water-soluble polymer may be 1,200,000 to 4,000,000 g / mol, 1,300,000 to 4,000,000 g / mol, 1,500,000 to 4,000,000 g / mol, 1,800,000 to 4,000,000 g / mol, 2,000,000 to 4,000,000 g / mol, 2,100,000 to 3,800,000 g / mol, or 2,200,000 to 3,600,000 g / mol.

[0076] Based on the total weight of the water-soluble polymer solution, the content of the water-soluble polymer contained in the water-soluble polymer solution may be 0.2 to 2 wt%, 0.4 to 1.5 wt%, 0.5 to 1.3 wt%, 0.5 to less than 1 wt%, or 0.6 to 0.95 wt%, but is not limited thereto. Since the content of the water-soluble polymer is within the above range, the strength of the composite can be ensured while improving the dispersibility of the composite in the solvent.

[0077] The solvent contained in the water-soluble polymer solution may be a common aqueous solvent (such as water, distilled water, etc.), but is not limited thereto.

[0078] At the same time, the water-soluble polymer solution and the biodegradable particles may be mixed so that a weight ratio (a:b) of the water-soluble polymer (a) to the biodegradable particles (b) contained in the water-soluble polymer solution is 40:60 to 95:5, 45:55 to 95:5, 45:55 to 90:10, 50:50 to 90:10, 55:45 to 85:15, 60:40 to 85:15, 65:35 to 85:15, 70:30 to 85:15, 75:25 to 85:15, 80:20 to 85:15 or 70:30 to 80:20.

[0079] The step (5) is a step of filling the mixed solution into a container. Specifically, the step (5) can be achieved by filling the mixed solution into a specific container to form a composite having a cake-like dosage form.

[0080] The container may specifically be a sealable glass bottle (such as a vial), but is not limited thereto.

[0081] Based on the total volume of the container, the filling amount of the mixed solution in the container can be 10% to 80% by volume, 15% to 70% by volume, 15% to 65% by volume, 20% to 60% by volume, or 25% to 55% by volume, but is not limited thereto. Since the filling amount of the mixed solution is within the above range, a composite having a desired compressive strength can be formed in a cake-shaped dosage form.

[0082] The step (6) is a step of freezing the mixed solution filled in the container and then drying (evaporating) the solvent under vacuum to form a composite having a cake-like dosage form. Specifically, the step (6) may include: (6-1) freezing the mixed solution at -60 to -10°C to obtain a frozen body; (6-2) heating the frozen body to -5 to 5°C for a first time in a vacuum environment for 1 to 3 hours; (6-3) heating the frozen body heated for the first time to 20 to 25°C for a second time in a vacuum environment for 8 to 15 hours; and (6-4) drying the frozen body heated for the second time at 25°C or higher in a vacuum environment for 20 to 40 hours.

[0083] The temperature of freezing the mixed solution in the step (6-1) may be -60 to -10°C, -50 to -20°C or -40 to -30°C, but is not limited thereto. In addition, the time for freezing the mixed solution may be 60 to 240 minutes, 90 to 180 minutes or 120 to 150 minutes, but is not limited thereto.

[0084] Described step (6-2) to described step (6-4) is the step of drying (evaporating) the solvent present in described frozen body by gradually increasing the temperature of described frozen body.At this moment, the final vacuum degree of each step can be 0.1 to 30mtorr, 0.5 to 20mtorr or 1 to 10mtorr, but is not limited to this.

[0085] Specifically, step (6-2) can be achieved by a first heating process in a vacuum environment over 1 to 3 hours or 1.5 to 2.5 hours to raise the temperature of the frozen body from -60 to -10°C to -5 to 5°C, -3 to 3°C or -1 to 1°C.

[0086] The step (6-3) can be achieved by heating the frozen body after the first heating to 20 to 25° C., 22 to 25° C. or 24 to 25° C. for a second time in a vacuum environment within 8 to 15 hours or 9 to 11 hours.

[0087] The step (6-4) can be achieved by raising the temperature of the frozen body after the second heating to 25° C. or higher (specifically 25 to 30° C.) within 20 to 40 hours or 22 to 30 hours in a vacuum environment and finally drying it.

[0088] Since freeze-drying of the mixed solution is performed through the steps (6-1) to (6-4), a composite having a cake-like dosage form can be efficiently formed.

[0089] Meanwhile, the method for manufacturing the composite according to the present invention may further include a step of sterilizing the composite.

[0090] The sterilization may be performed by gamma ray sterilization, electron beam (e-beam) sterilization, ethylene oxide sterilization, steam sterilization or high pressure steam sterilization, but is not limited thereto. Specifically, the sterilization may be performed using ethylene oxide at a temperature of 30 to 40° C. for 150 to 180 minutes. This process may further improve the long-term storage capability of the compound.

[0091] The size of the biodegradable particles contained in the composite prepared by the manufacturing method is not particularly limited, but the average particle diameter (Dv(50)) may be 15 to 60 μm. Specifically, the biodegradable particles may be first biodegradable particles whose Dv(50) particle size distribution is 15 to 30 μm, 17 to 29 μm, 18 to 28 μm, 19 to 27 μm, 20 to 25 μm or 21 to 23 μm; second biodegradable particles whose Dv(50) particle size distribution is greater than 30 to 60 μm, greater than 30 to 55 μm, 35 to 50 μm, 35 to 48 μm, 38 to 45 μm or 40 to 43 μm; or mixtures thereof, but are not limited thereto.

[0092] Specifically, according to Formula 1, the particle size distribution (PSD) of the biodegradable particles contained in the composite prepared by the manufacturing method can be 0.4 to 2.5, 0.5 to 2.2, 0.6 to 2.0, 0.65 to 1.9, 0.7 to 1.8, 0.8 to 1.7, 1.0 to 2.5, 1.0 to 2.3, 1.0 to 2.0, 1.01 to 1.6, 1.02 to 1.5, 1.03 to 1.4 or 1.05 to 1.3, but is not limited thereto.

[0093] <Formula 1>

[0094] PSD = (Dv(90) - Dv(10)) / Dv(50)

[0095] In the formula 1,

[0096] Dv(10) is the size of the biodegradable particles within 10% of the distribution.

[0097] Dv(50) is the size within which 50% of the biodegradable particles are distributed.

[0098] Dv(90) is the size within which 90% of the biodegradable particles are distributed.

[0099] In the present invention, a composite is prepared by filling a mixed solution obtained by mixing biodegradable particles having a specific particle size distribution with a water-soluble polymer solution into a sealable container and freeze-drying it, thereby obtaining a composite having a cake-like dosage form with a specific morphology and controllable compressive strength.

[0100] Since the composite of the present invention has a cake-like dosage form, it has good long-term storage and dispersibility, and improves handling convenience by controlling the compressive strength. In addition, since the composite of the present invention contains biodegradable particles and a water-soluble polymer, it has biocompatibility and biodegradability.

[0101] Therefore, the composite according to the present invention can be well used as a material for restoring or replacing human tissue. In addition, the composite according to the present invention can also be used as a carrier of cells or drugs, a cell culture medium, etc.

[0102] Cosmetic filling composition

[0103] The present invention provides a cosmetic filling composition in which the complex is dispersed. Specifically, the cosmetic filling composition according to the present invention may be a composition in which the complex having the same components and properties as above is dispersed in a solvent.

[0104] Due to the enhanced dispersibility of the composite, the cosmetic filling composition according to the present invention can be prepared in a short time (e.g., within 30 minutes). That is, since a sealed composite having a solid phase cake-shaped dosage form is used, the solubility and dispersibility are enhanced, so that the cosmetic filling composition can be prepared in a short time, and therefore, the present invention can prepare the cosmetic filling composition immediately before surgery. In addition, since the composite contains biodegradable particles with a controllable particle size distribution, the cosmetic filling composition obtained by dispersing it in a solvent can easily complete the surgery by applying less force to the syringe even with a needle having a thinner diameter. Therefore, the cosmetic filling composition according to the present invention can reduce the discomfort and fatigue of the operator and improve the operating environment.

[0105] For example, according to the cosmetic filling composition of the present invention (e.g., a composition in which a complex having an average particle diameter (Dv(50)) of 60 μm or less is dispersed), the injection force may be 2.0 N or less, specifically, 0.3 to 1.5 N, 0.5 to 1.3 N, 0.7 to 1.25 N, or 0.9 to 1.20 N for an injection needle having a needle gauge (G) of 26, but is not limited thereto. In addition, according to the cosmetic filling composition of the present invention (e.g., a composition in which a complex having an average particle diameter (Dv(50)) of 33 μm or less is dispersed), the injection force may be 3.0 N or less, specifically, 1.6 to 2.6 N, 1.7 to 2.4 N, 1.8 to 2.2 N, or 1.9 to 2.0 N for an injection needle having a needle gauge (G) of 30, but is not limited thereto.

[0106] Mode for carrying out the invention

[0107] The present invention will be described in detail below by way of examples, but the scope of the present invention is not limited to the examples.

[0108] Example 1

[0109] 9 g of polylactic acid (PLA) with a weight average molecular weight of 170,000 g / mol was dissolved in 150 ml of a mixed solvent of dimethyl sulfoxide and ethylene carbonate in a weight ratio of 90:10 to prepare a polylactic acid solution.

[0110] Then, the prepared polylactic acid solution was sprayed into normal hexane cooled to -20°C or lower with a spraying amount of 4.5 ml / min and a spraying air amount of 6 L / min to form frozen polylactic acid particles in normal hexane. The formed frozen polylactic acid particles were added to water at 1 to 3°C and stirred to remove the mixed solvent (dimethyl sulfoxide + ethylene carbonate) contained in the frozen polylactic acid particles, thereby preparing polylactic acid particles (PLA particles).

[0111] Subsequently, the prepared polylactic acid particles were sorted using a particle sorter to obtain polylactic acid particles having a particle diameter of 60 μm or less (Dv(50): 41.9 μm).

[0112] Then, polylactic acid particles having a particle diameter of 60 μm or less are added to a 0.6% sodium hyaluronate solution (HA solution = 99.4 wt % distilled water + 0.6 wt % sodium hyaluronate) so that the weight ratio of polylactic acid particles to sodium hyaluronate (HA) is 85:15, and then they are mixed to prepare a mixed solution.

[0113] Then, 5.20 g of the prepared mixed solution (170 mg PLA particles + 30 mg HA) was charged into a 10 ml vial.

[0114] Then, the mixed solution in the vial was frozen at a temperature of -40 to -30°C to obtain a frozen body. The obtained frozen body was first heated from -30°C to 0°C in 2 hours in a vacuum environment, then heated from 0°C to 25°C for a second time in 10 hours, and then dried at 25°C for 24 hours to form a complex in the vial.

[0115] Then, the vial containing the composite was sterilized using ethylene oxide (EO) gas, and residual moisture was removed by vacuum drying to prepare a composite having a diameter of 1.8 cm and a height of 2.2 cm.

[0116] Example 2 to Example 4

[0117] The composite was prepared by the same process as in Example 1, except that the concentration of sodium hyaluronate (HA) contained in the mixed solution filled in the vial, the amount of the mixed solution filled, and the diameter and height of the composite were adjusted as shown in Table 1 below.

[0118] [Table 1]

[0119]

[0120] Example 5

[0121] A composite having a diameter of 1.8 cm and a height of 0.55 cm was prepared by the same process as in Example 1, except that the polylactic acid particles were sorted using a particle sorter to obtain polylactic acid particles having a particle diameter of 33 μm or less (Dv(50): 21.1 μm), which were added to a sodium hyaluronate solution.

[0122] Comparative Example 1

[0123] A composite with a diameter of 1.8 cm was prepared by the same steps as in Example 1, except that the mixed solution (170 mg PLA particles and 30 mg HA) was filled into a vial and vacuum dried at 25° C. for 16 h (ie, freeze drying and sterilization processes were not performed).

[0124] Experimental Example 1. Dosage Form Confirmation

[0125] The dosage forms of the composites prepared in Examples 1, 5 and Comparative Example 1 were visually confirmed. Figure 2 shown.

[0126] Reference Figure 2, the composites of Example 1 and Example 5 are in a cake-like dosage form (cylindrical). In contrast, the composite of Comparative Example 1 has no regular shape because the mixed solution expands during the vacuum drying process.

[0127] Here, since the composites in Examples 1 and 5 have a cake-like dosage form, the present invention can improve the dispersibility and ease of use of the composites, which can be confirmed in Experimental Examples 7 and 8 below.

[0128] Experimental Example 2. Confirmation of the internal structure of polylactic acid particles and the structure of the composite

[0129] The composites prepared in Example 1 and Example 5 were cut vertically, and the cross-sections were observed using a scanning electron microscope (manufacturer: Hitachi High Technologies, model: Hitachi su5000). Figure 3 and Figure 4 shown.

[0130] Reference Figure 3 and Figure 4 From a) in Example 1 and Example 5, it can be confirmed that the polylactic acid particles each maintain their shape and are uniformly present inside the composite.

[0131] In addition, refer to Figure 3 and Figure 4 From b), it can be confirmed that the polylactic acid particles present in the composites of Examples 1 and 5 have a network structure inside.

[0132] Experimental Example 3. Determination of tap density

[0133] In Example 1 and Example 5, the tap density of the polylactic acid (PLA) particles obtained by sorting with a particle sorter was measured according to the following measurement method. The results are shown in Table 2 below.

[0134] *Tap density determination method

[0135] 1) Measure the weight of the measuring cylinder and put 20 to 25 ml of polylactic acid particles into the measuring cylinder.

[0136] 2) Determine the weight of the measuring cylinder containing the polylactic acid particles and calculate the weight of the pure polylactic acid particles.

[0137] 3) The measuring cylinder containing the polylactic acid particles was mounted on a tap density meter (manufacturer: Bettersize, model: BeDensi T1 Pro).

[0138] 4) The tap density meter was operated at a tapping speed of 250 times / minute and a tapping frequency of 1,250 times.

[0139] 5) After compaction, take out the measuring cylinder and measure the volume of the polylactic acid particles.

[0140] 6) Divide the weight of the polylactic acid particles measured in step 2) by the volume of the polylactic acid particles measured in step 5) to calculate the tap density (measure the tap density of 5 samples separately and obtain the average value).

[0141] [Table 2]

[0142]

[0143] Referring to Table 2 above, it can be confirmed that the tap density of the polylactic acid particles prepared in Example 1 and Example 5 is between 0.1 and 0.2 g / ml. In Example 5, the particle size of the polylactic acid particles is smaller than that in Example 1, so the tap density of the polylactic acid particles is larger, and high-density bonding is expected to be achieved inside the composite.

[0144] Experimental Example 4. Particle size distribution measurement

[0145] The particle size distribution of the polylactic acid particles prepared in Example 1 and Example 5 was measured according to the following measurement method. The results are shown in Table 3 below.

[0146] * Particle size distribution determination method

[0147] 1) Add the complex into water and stir for 30 minutes to prepare a suspension.

[0148] 2) The prepared suspension was analyzed using a particle size distribution analyzer (manufacturer: Malvern Instrument, model: Mastersizer 3000-Maz 6140) to determine the particle size distribution of the polylactic acid particles.

[0149] 3) According to the values ​​measured in step 2), the particle size distribution (PSD) is calculated using the following formula 1.

[0150] <Formula 1>

[0151] PSD = (Dv(90) - Dv(10)) / Dv(50)

[0152] In the formula 1,

[0153] Dv(10) is the size of the biodegradable particles within 10% of the distribution.

[0154] Dv(50) is the size within which 50% of the biodegradable particles are distributed.

[0155] Dv(90) is the size within which 90% of the biodegradable particles are distributed.

[0156] [Table 3]

[0157] distinguish Dv(10) Dv(50) Dv(90) Particle size distribution Example 1 20.9μm 41.9μm 73.9μm 1.265 Example 5 11.6μm 21.1μm 34.4μm 1.081

[0158] Referring to Table 3 above, it can be confirmed that the particle size distribution range of the polylactic acid particles prepared in Example 1 and Example 5 is 1.0 to 2.5. Among them, since the particle size distribution of the polylactic acid particles is within the above range, the present invention can improve the convenience of use (practicality) of the composite. That is, when the particle size distribution is within the above range, the dispersibility of the composite is very good, and even if a small force (injection force) is applied to the syringe containing the suspension dispersed with the composite, the suspension can be discharged smoothly, which can be confirmed in the following Experimental Examples 7 and 8.

[0159] Experimental Example 5. Compressive Strength Determination

[0160] The compressive strength of the composites prepared in Examples 1 to 4 and Comparative Example 1 was measured using an Instron 5848 (model name) instrument (measurement conditions—compression speed: 10 mm / min, maximum compression rate: 75%). The results are shown in Table 4 below.

[0161] [Table 4]

[0162] distinguish HA concentration (%) Compressive strength(MPa) Example 1 0.6 0.03750 Example 2 0.8 0.36316 Example 3 1.0 0.50605 Example 4 1.2 0.94671 Comparative Example 1 0.6 Unable to measure (irregular shape)

[0163] Referring to Table 4 above, it can be confirmed that the compressive strength of the composites in Examples 1 to 4 is between 0.03 and 1 MPa. In addition, it can be seen that the concentration of sodium hyaluronate (HA) has an effect on the compressive strength of the composite.

[0164] Meanwhile, since the composite of Comparative Example 1 had an irregular shape, the compressive strength could not be measured.

[0165] Experimental Example 6. Apparent volume measurement

[0166] The apparent volumes of the composites prepared in Examples 1 to 4 and Comparative Example 1 were measured using the diameter and height of the composites. The results are shown in Table 5 below.

[0167] [Table 5]

[0168] HA concentration (%) Apparent volume (ml / g) Example 1 0.6 27.9 Example 2 0.8 17.0 Example 3 1.0 15.2 Example 4 1.2 10.1 Comparative Example 1 0.6 Unable to measure (irregular shape)

[0169] Referring to Table 5 above, it can be confirmed that the apparent volume of the composites in Examples 1 to 4 ranges from 10 to 40 ml / g. In addition, it can be understood that in order to increase the porosity of the composite, it is best to reduce the concentration of sodium hyaluronate (HA). Among them, if the composite has a higher porosity, it can be quickly suspended in an aqueous solvent for use, thereby improving the convenience of use of the composite, which can be confirmed in the following Experimental Examples 7 and 8.

[0170] Meanwhile, since the composite of Comparative Example 1 has an irregular shape, the apparent volume cannot be determined.

[0171] Experimental Example 7. Suspension time measurement

[0172] The suspension time of the composites prepared in Examples 1 to 4 and Comparative Example 1 was measured according to the following measurement method. The results are shown in Table 6 below.

[0173] * Suspension time determination method

[0174] 1) Add 8 ml of distilled water to the vial containing the complex and let it stand for about 5 minutes.

[0175] 2) After setting the rotation speed (rpm) of the vortex stirrer to 3,000, stir the vial for 5 minutes.

[0176] 3) Visually confirm whether the complex in the vial is completely dissolved and granulated.

[0177] 4) Repeat the process of step 2) until the complex is completely dissolved, and measure the time required for its granulation.

[0178] [Table 6]

[0179]

[0180] Referring to Table 6 above, the complexes in Examples 1 to 4 are all rapidly suspended (dispersed) within a suspension time of 30 minutes or less. Since the suspension is completed in a short time, the complex of the present invention has excellent convenience in use. For example, when the complex is suspended in an aqueous solvent at the surgical site for skin surgery, it can be suspended in a short time, thereby improving the efficiency of the surgery.

[0181] Among them, since the composite of the present invention has a cake-like dosage form, and the particle size distribution, compressive strength and apparent volume are within a specific range, it can be suspended in a short time, which proves the importance of controlling the shape, compressive strength, apparent volume and particle size distribution of the composite.

[0182] In addition, it was confirmed that the lower the concentration of sodium hyaluronate (HA), the shorter the suspension time. Therefore, in order to improve the ease of use of the composite, it is best to control the concentration of hyaluronic acid that constitutes the composite support structure (framework).

[0183] Experimental Example 8. Injection force measurement

[0184] The injection force of the composites prepared in Example 1 and Example 5 was measured according to the following measurement method. The results are shown in Table 7 below.

[0185] *Injection force measurement method

[0186] 1) Add 5 ml of distilled water to the vial containing the complex and stir with a vortex mixer until the complex is dissolved and granulated (suspension preparation).

[0187] 2) Inject 0.5 to 0.6 ml of the suspension in the vial into a 1 ml disposable syringe.

[0188] 3) Install a 26G or 30G injection needle on the syringe, and fix the syringe on the bracket of the universal testing machine (manufacturer: TestOne, model: TO-102) with the needle facing downward.

[0189] 4) Operate the universal testing machine, press the push rod on the syringe at a speed of 1 mm / s until the syringe is completely empty, and record the measured force.

[0190] 5) In the graph recording the measured forces, calculate the average value (injection force) of the forces measured at 5 mm to the right of the starting point, 5 mm to the left of the end point, and the midpoint between the two points.

[0191] [Table 7]

[0192]

[0193]

[0194] Referring to Table 7 above, the injection force of the complexes of Example 1 and Example 5 is relatively small, so even if a relatively small injection force is applied, the suspension in which the complex is dispersed can be smoothly discharged from the syringe. Due to the small injection force, the complex of the present invention has excellent convenience in use. For example, when the suspension in which the complex is dispersed is used at the surgical site, even if a relatively small force is applied to the syringe, the suspension can be smoothly discharged from the syringe and injected into the skin, thereby improving the convenience of the surgery.

[0195] The above results also demonstrate the importance of controlling the shape, compressive strength, apparent volume and particle size distribution of the composites.

Claims

1. A composite comprising: Biodegradable particles, each of which has a mesh structure inside; as well as Water-soluble polymers, The weight ratio of the biodegradable particles to the water-soluble polymer is 60:40 to 85:15, The biodegradable particles include polylactic acid, The water-soluble polymer includes hyaluronic acid, The compressive strength of the composite is 0.02 to 0.36316 MPa, The apparent volume of the complex is 17 to 40 ml / g, And has a cake-like dosage form.

2. The composite according to claim 1, wherein The tap density of the biodegradable particles is 0.1 to 0.25 g / ml.

3. The composite according to claim 1, wherein The suspension time of the complex in the aqueous solvent is 30 minutes or less.

4. A method for producing the composite according to claim 1, comprising the following steps: (1) dissolving a biodegradable raw material in a first solvent to prepare a biodegradable solution; (2) spraying the biodegradable solution into a second solvent having a freezing point lower than that of the first solvent to form biodegradable particles having a network structure inside; (3) screening the biodegradable particles by size; (4) adding the biodegradable particles screened by size to a water-soluble polymer solution to prepare a mixed solution; (5) filling the mixed solution into a container; as well as (6) freeze-drying the mixed solution filled in a container to form a composite having a cake-like dosage form, In the step (4), the content of the water-soluble polymer in the water-soluble polymer solution is 0.2% to 0.8% by weight of the total weight of the water-soluble polymer solution. The biodegradable particles include polylactic acid, The water-soluble polymer includes hyaluronic acid.

5. The method for producing a complex according to claim 4, wherein the step of freeze-drying the mixed solution in step (6) comprises the following steps: (6-1) freezing the mixed solution at -60 to -10°C to obtain a frozen product; (6-2) in a vacuum environment, heating the frozen product to -5 to 5° C. for a first time for 1 to 3 hours; (6-3) in a vacuum environment, heating the frozen body heated for the first time to 20 to 25° C. for a second time for 8 to 15 hours; as well as (6-4) The second heated frozen body is dried at 25° C. or higher for 20 to 40 hours in a vacuum environment.

6. A cosmetic filling composition, wherein: The composite according to any one of claims 1, 2 and 3 is dispersed therein.

Citation Information

Patent Citations

  • Method for producing polymer microparticles having network structure

    CN108350180A

  • Manufacturing method of polymeric microparticles having network structure

    KR101725279B1

  • Freeze-dried product for filler, preparing method thereof, and injection for filler including the same

    KR102266386B1

  • Hybrid hydrogel injection for dermal filler application based on hyaluronic acid containing biodegradable polymer microparticle and method for preparing the same

    KR102403554B1